Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Kimia Dan Sub Sektor Farmasi Yang Terdaftar Di BEI Periode 2016-2019) - Eva Susanti; Ronny Malavia Mardani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe research purposes to look for a relationship between profitability (X1), liquidity (X2), free cash flow (X3) on dividend policy (Y). The type of research used is explanative quantitative research. plays a role in explaining the influence of the independent variables on the dependent variable. The data obtained through a quantitative approach, in testing using numbers with statistical techniques. The sample selection technique uses a purposive sampling technique with the criteria of companies that pay dividends consecutively in the 2016-2019 period, the chemical sub-sector companies and the pharmaceutical sub-sector listed on the IDX and have complete data regarding the required calculation indicators, financial reports expressed in rupiah currency, in order to obtain 10 companies. The data analysis techniques in this study used descriptive tests, classical assumption tests, multiple linear regression tests and hypothesis testing. From data management, it is found that profitability has a significant negative effect on dividend policy. liquidity and free cash flow have a negative and insignificant effect on dividend policy. Kata kunci: Profitabilitas, Likuiditas, Free Cash Flow, Kebijakan Dividen.